Filmes de polianilina depositados por método de banho químico assistido por ultrassom : efeito da concentração de ácido sobre propriedades eletroquímicas - Souza, Marcos Fabio Farias (2023)
The growth of renewable energy's share in the global energy mix increases the demand for energy storage technologies to overcome intermittency in wind and solar power generation. In this context, supercapacitors stand out as an intermediate technology between conventional capacitors and rechargeable batteries. Polyaniline (PANI) is a conductive polymer with promising properties for applications as an electrode material in supercapacitors, such as high specific capacitance and good electrical conductivity. However, it exhibits low cyclic stability, so PANI-based electrode materials are widely studied, either in doped form or as composites, to improve cyclic stability. Therefore, in the present study, the effect of sulfuric acid concentration (dopant) on the structural, morphological, and electrochemical properties of PANI films deposited on stainless steel substrates through ultrasound-assisted chemical bath deposition was evaluated for supercapacitor study. Structural characterization of the films by Fourier-transform infrared spectroscopy (FTIR) and ultraviolet-visible (UV-vis) spectroscopy revealed that polyaniline was obtained in the emeraldine form. The lower acid concentration led to a granular morphology, while the higher concentration resulted in a predominance of porous fiber networks, as observed by scanning electron microscopy (SEM) analysis. Cyclic voltammetry (CV) identified the redox process and demonstrated the pseudocapacitive behavior of the films. Galvanostatic charge-discharge tests indicated that higher acid concentration in the reaction medium led to higher specific capacitance, with a maximum value of 531 F g-1. The higher acid concentration was also associated with lower charge transfer resistance, improved capacitive behavior, and higher capacitance at low frequency, according to the electrochemical impedance spectroscopy (EIS) results. Finally, a symmetric supercapacitor device was assembled using electrodes synthesized with the highest acid concentration. The potential for application in supercapacitors was highlighted energy and power density values of 11.5 Wh/kg and 241 W/kg at 0.5 A g-1, respectively. Additionally, it demonstrated excellent cyclic stability, achieving a capacitance retention of 106% after 1000 continuous charge and discharge cycles at 5 A g-1.